The Richness, Similarity, and Conservation Status of the Herpetofauna of the Balsas Basin Biogeographic Province of Mexico - Julio A. Lemos-Espinal; Geoffrey R. Smith (Diversity)
The Balsas Basin (BB) is a biogeographic province in south-central Mexico that straddles the Mexican Transition Zone and the Neotropical region. We provide a list of the amphibian and reptile species of the BB based on a detailed review and update of recent species lists of its constituent states. The BB is home to 51 native amphibian and 155 native reptile species, which represent 14.7% of the herpetofauna of Mexico. No amphibian and six reptile species are endemic to the BB. Six species of amphibians and seven of reptiles are categorized as being of conservation concern status (vulnerable, endangered, or critically endangered) on the International Union for Conservation of Nature’s (IUCN) Red List. The main threat these species face is habitat loss due to urbanization, agriculture, and pollution. The herpetofauna of the BB shows significant overlap with neighboring provinces. The composition of amphibian species in the BB is closest to that of the Pacific Lowlands, whereas the composition of reptile species is closest to the Sierra Madre del Sur and the Transvolcanic Belt. These findings suggest that while the BB supports significant amphibian and reptile diversity, its conservation importance may be limited due to the low levels of endemism and the relatively small proportion of species at risk.